Implementation of Environmental Law in Mineral and Coal Mining - Moh. Taufik (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
Mining materials as natural resources that cannot be renewed and have limited quantities of course have very high economic value. The existence of this high economic value is a factor in the mining business becoming an industry, both by the government and the private sector. The application of Environmental Law to mineral and coal mining is very important, so as not to cause environmental problems. This research aims to see how environmental law is applied to mineral and coal mining. This research includes library research because the data used is mostly secondary data in the form of legal documents as well as reviewing empirical data in the field. The analysis used uses a qualitative approach. The results of this research are that mineral and coal mining needs to implement environmental law properly, to avoid wider environmental problems. The stages in implementing environmental law, starting from completing environmental impact analysis, issuing IUP, preparing mining road infrastructure and reclamation after mining.